Investigation of pine (Pinus nigra) bark extracts containing phenolic compounds - Amlani, Merilyn (Kastamonu Üniversitesi, 2022)
Chemical pollution, which occurs in proportion to the increase in the rate of industrialization seen today, and the increase in the duration and amount of exposure, seriously affect human health. The public's awareness of the relevance of the issue is caused by the direct or indirect interaction of chemicals like poisonous, carcinogenic, and pesticides with nature. It is not only for the elimination of these reservations and the protection of health; At the same time, it is the most basic approach to use plants in studies made as a result of the body's vitality and effort to live longer, and this approach is as old as human history. As a result, today's interest in food has shifted from providing the nutrients needed to sustain life and growth to preventing or actually curing various types of disease. Moreover, recent technological advances, lifestyle changes in the population and socio-economic trends worldwide indicate the growing need for foods with health benefits. Even if for people with unhealthy eating habits beyond a healthy diet, supplemental products are recommended to eliminate the harmful effects of metabolic reactive oxygen species. In short, it is desired that nutrition reduces oxidative stress in a straightforward way. Within the subject, the interest in the so-called “natural” products that are potentially under-processed has increased tremendously. As a result, herbal supplements have gained acceptance as an alternative to synthetic medications and have established a market for themselves, even if research on their therapeutic effects is still ongoing. The bioactive compounds found in plants have been used by humans from the earliest times to treat a variety of diseases naturally in addition to providing food and shelter. These bioactive substances, which are important in various fields, are formed as a result of crucial metabolic processes in plants. As a result of different chemical reactions, they have a wide variety and are classified as primary and secondary metabolites. Plants; through primary metabolism, they produce primary metabolites, including carbohydrates, proteins, lipids, and other organic acids that are essential for both human nutrition and the growth and development of plants. On the other hand, plants' secondary metabolism also helps to produce secondary metabolites, including terpenes, compounds that contain nitrogen, and phenolic compounds (PCs). These compounds are not directly important for plant growth and development. However, they are important for their ecological function as an attractant, pollinator, and even protecting plants from anything that could harm them. In addition, these compounds, especially PCs, are widely used in different fields such as pharmacology, cosmetics and the food industry. PCs are widely used as an active ingredient in the pharmacological field due to their various therapeutic functions such as anti-inflammatory, anticancer, anti-proliferative, antidiabetic and, most importantly, their antioxidant capacity. The use of PCs in the food industry has also become widespread due to their antioxidant capacity, which can be used as an alternative to synthetic antioxidants in the protection of food products containing high unsaturated fatty acids prone to oxidation. Therefore, an increasing number of studies are carried out on these substances in terms of their biological effects and natural resources. PCs are found in a variety of plant species, including herbs, shrubs, trees, and others. These include species such as pine trees that are often used as potential sources of PCs. Pinus pinaster and Pinus maritima are pine tree species that attract attention for the abundance of PCs. The bark of this tree is a great source of proanthocyanidin compounds and is sold commercially as dietary supplements under the trade name Pycnogenol (PYC). With the demand and popularity of this pine tree, other pine tree species have also been discovered as potential sources of PCs. One of them is Pinus nigra. P. nigra, the second most abundant pine species in Türkiye, is especially common in Küre and Ilgaz Kastamonu National Parks. It has a total forest area of 4.7 million hectares and is one of the important pine tree species in the wood industry. P. nigra is already used in traditional Turkish medicine to treat a variety of conditions, including respiratory, gastrointestinal, and back problems. PCs can be found in various plant parts. According to various studies, pine tree components such as needles, cones, roots and especially bark can be used as possible sources of PCs. Pine bark, which constitutes 9-15% of the waste by-product in the wood sector, is an ideal source to be used to reduce waste and obtain products rich in PCs with high added value. Different methods, such as conventional and non-traditional extraction methods, are used for the isolation of PCs. While unconventional methods are advantageous in terms of shorter extraction time, less solvent usage and other aspects, traditional methods such as maceration are still widely used today due to their simplicity and accessibility. In this work, P. nigra bark extracts (PNBE) abundant in the province of Kastamonu, Türkiye, particularly in Ilgaz and Küre national parks, were used as a potential plant source of PCs and aimed to utilize it to establish a cost-effective and efficient way to extract. The PNBE was extracted using maceration (MAC), where the effects of time, temperature, and solvent concentrations on the total phenolic contents (TPC) and 2,2-diphenyl-1- picrylhydrazyl (DPPH) antioxidant capacity was optimized using response surface methodology (RSM). The extraction yield (EY) (6.40 ± 0.66% d.w), diffusion coefficients (𝐷௘௙௙) (1.01 x 10-12 m2 /s), TPC (42.56 ± 1.13 mgGAE/100g d.w), DPPH (IC50 6.24 ± 0.04 µgAAE/ml), and FRAP (18.42 ± 0.56 mgAAE/100g d.w) antioxidant capacity were determined using the optimized parameters at 60% EtOH, 240 mins, and 60°C, with constant solid/liquid ratio (100 g/L) and particle size (0.250-0.500 mm). Analysis in phenolic profiling using reverse phase high-performance liquid chromatography (RP-HPLC-DAD) revealed that 2,5 dihydroxybenzoic acid, myricetin, catechin, naringin, and ferulic acid are the major components in PNBE, accounting for 19.42, 19.33, 16.88, 11.04, and 10.15% of the total amount measured, respectively, while others are less than 10%. For SPME-GC-MS, there were four main peaks detected: decane, dodecane, tetradecane, and hexadecane, with 8.30, 15.71, 19.00, and 7.92% total area detected, respectively. Compounds such as phenol and terpenes, including the cadinene family of sesquiterpenes, which made up 0.98 and 0.24% of the total area, were also observed. Antibacterial properties of PNBE were also assessed, and it was found that their ability to stop bacterial development is less effective than that of other pine species. Furthermore, heavy metals such as As, Cr, Cd, Cu, and Pb were found in PNBE with concentration levels of 192 ± 3.49, 94.85 ± 0.61, 16.65 ± 0.05, 177.62 ± 1.22, and 215.82 ± 0.53 ppb, respectively. These concentrations are less than the acceptable levels established by the World Health Organization (WHO), European Union (EU), and Codex Stan 193-1995. Based on the findings of this study, it can be concluded that PNBE is an excellent source of PCs that are very important for pharmacological uses, especially the finding of the antioxidant ability of in-vitro analysis. The impacts of various variables and amounts are also demonstrated for the various PCs in PNBE. According to the completed study, ideal conditions were obtained for the extraction of PNBE using the RSM technique. This optimization technique has been identified as an effective approach to intensify different extraction factors. The presence of heavy metals in PNBE may pose a risk to human health because pine species extracts are essential for many medicinal applications. Additionally, PNBE has been found to have the antibacterial capacity, but at some points their ability to inhibit bacterial growth is less effective than other strains. In conclusion, this study is significant because it demonstrates that high value-added products can be produced using a simple extraction method, such as the maceration of tree bark which is considered a waste product of the timber industry. Only in this way, it should be tested with further studies supporting its applicability in nutraceutical and cosmetic products in order to prevent damage caused by oxidative stress in the human organism and more. Finally, another important result of this study is that the commercially imported product substitution was made in Kastamonu, which includes the Ilgaz and Küre national parks.
Fenolik bileşikler içeren karaçam (Pinus nigra) kabuğu ekstraktlarının incelenmesi
Keywords: Pine Bark Extracts, Pinus nigra, Vitamin P, Phenolic compounds, Antioxidant, Antibacterial, Heavy Metals